Answer:
1. (a² - b)/(a³b²)= 1/ab² - 1/a²b
2. (b - a)/a³b³ = 1/a³b² - 1/a²b³
3. (2 - ab²)/(a²b³) = 2/a²b³ - 1/ab
4. (2 - a)/a³b³ = 2/a³b³ - 1/a²b³
Explanation:
To do this we'll break down fraction to least term through division.
The solution is as follows
1. (a² - b)/(a³b²)
Splitting the fraction;
a²/a³b² - b/a³b²
= 1/ab² - 1/a²b
2. (b - a)/a³b³
Splitting the fraction.
b/a³b³ - a/a³b³
1/a³b² - 1/a²b³
3. (2 - ab²)/(a²b³)
Splitting the fraction.
2/a²b³ - ab²/a²b³
2/a²b³ - 1/ab
4. (2 - a)/a³b³
Splitting the fraction
2/a³b³ - a/a³b³
2/a³b³ - 1/a²b³